1997
DOI: 10.1088/0031-9155/42/7/008
|View full text |Cite
|
Sign up to set email alerts
|

Application of cavity theory to the response of various TLDs to gammas degraded in water

Abstract: Several types of thermoluminescent dosimeters (LiF:Mg, Ti, Al2O3:Mg,Y and CaF2:Mn) were irradiated at different depths in a water phantom placed at a distance of 2.5 m from a panoramic 60Co source. Detectors were encapsulated in Plexiglas holders with a wall thickness of 0.5 cm. Reference dosimetry was carried out using a Fricke dosimeter and an ionization chamber. The experimental data were compared with the predictions of the general cavity theory for gamma ray spectra at different depths of water. The suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…This is coincident with our results. Using the cavity theory of Horowitz-Dubi, MILIANIC et al [4] showed that in 60 Co γ beams the absorbed dose ratio factor of the Al 2 O 3 dosimeter was 1.147 (a reciprocal of the original data D d /D m = 0.872), which is also in good agreement with our results.…”
Section: Discussionsupporting
confidence: 91%
“…This is coincident with our results. Using the cavity theory of Horowitz-Dubi, MILIANIC et al [4] showed that in 60 Co γ beams the absorbed dose ratio factor of the Al 2 O 3 dosimeter was 1.147 (a reciprocal of the original data D d /D m = 0.872), which is also in good agreement with our results.…”
Section: Discussionsupporting
confidence: 91%
“…k Q can be determined empirically or by using cavity theory, 24 where the dose to the cavity is due to both electrons crossing the cavity and secondary electrons created within the cavity. 30,31 When using the cavity theory approach, the calculated dose to the dosimeter (D Al 2 O 3 :C ) is the dosimeter signal, and thus, the correction factor can be defined as follows [Eq. (6)]:…”
Section: D Beam Quality Dependence (K Q )mentioning
confidence: 99%
“…Burlin cavity theory consists of two components to account for both the dose that arises from the secondary electrons crossing the cavity and the dose from the secondary electrons that are created inside the cavity. Although many modifications of Burlin theory have been proposed, Miljanic and Ranogajec-Komor (8) found that the most general expression of Burlin cavity theory is in good agreement with experimental results; therefore, the general Burlin cavity theory shown in Equation (1) (8,12) was used to calculate the dose to the OSLD:…”
Section: Calculation Of Dose To Oslds Using Burlin Cavity Theorymentioning
confidence: 99%
“…In principle, correction factors can also be calculated using cavity theory, which has been used, in previous studies, to determine the energy dependence of other solid-state detectors (6 -11) . Burlin cavity theory is most appropriate for 'medium-sized' cavities, where the total dose is due to contributions from both photon and electron interactions inside the cavity (8,12) . Cavities of varying physical size can thereby be well approximated using this theory.…”
Section: Introductionmentioning
confidence: 99%